2006
DOI: 10.1186/1479-5868-3-15
|View full text |Cite
|
Sign up to set email alerts
|

The neighborhood food environment: sources of historical data on retail food stores

Abstract: With the rapidly increasing prevalence of obesity in the United States, and the minimal success of education-based interventions, there is growing interest in understanding the role of the neighborhood food environment in determining dietary behavior. This study, as part of a larger study, identifies historical data on retail food stores, evaluates strengths and limitations of the data for research, and assesses the comparability of historical retail food store data from a government and a commercial source.Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…Though the lack of home postcode data for 1980 may be considered a weakness of this study, the authors believe that it does not diminish the findings of this work, which uses a unique data set to illustrate changes in food intake and changes in BMI in relation to the changing food environment. A recent study has shown the importance of telephone directories as a reliable source of complete lists of stores, regardless of size (Wang, Gonzales et al 2006). However, Wang et al (2006) concede that these directories may give a considerably higher count of stores than actually exist because of stores that have advertised and subsequently closed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the lack of home postcode data for 1980 may be considered a weakness of this study, the authors believe that it does not diminish the findings of this work, which uses a unique data set to illustrate changes in food intake and changes in BMI in relation to the changing food environment. A recent study has shown the importance of telephone directories as a reliable source of complete lists of stores, regardless of size (Wang, Gonzales et al 2006). However, Wang et al (2006) concede that these directories may give a considerably higher count of stores than actually exist because of stores that have advertised and subsequently closed.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown the importance of telephone directories as a reliable source of complete lists of stores, regardless of size (Wang, Gonzales et al 2006). However, Wang et al (2006) concede that these directories may give a considerably higher count of stores than actually exist because of stores that have advertised and subsequently closed. Whilst this is a limitation, the fact that advertisements in the Yellow Pages have to be renewed annually makes it unlikely that the data were out of date and this was confirmed through e-mail correspondence with yell.com.…”
Section: Discussionmentioning
confidence: 99%
“…A company can specify to be listed under multiple classification categories, which can result in a gross overestimation of the number of outlets present, as described by Wang et al (2006). To overcome this potential problem here, and to reduce count error, if the same store was listed under multiple classification categories the outlet was only included once.…”
Section: Commercial Directoriesmentioning
confidence: 99%
“…This results in a large variety of outlets being incorporated including small outlets with low revenue. In the US, Wang et al (2006) used commercial databases which generally did not include retail food stores with an annual sales volume of under $500,000. This would not provide a true representation of the stores in a particular area as small retail food stores may not be included.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation